Peculiarities Of Women's Activities in The Field of Non-Manufacturing - Nafisa Abduxalilova Shonazarovna; Kalanova Sabohat Muradovna (Zien Journals, 2022)
In this article, the writer highlighted the important points of the women’s role in society, medicine, education and other special fields. In addition to this, while reading this article you will be able to get acquainted with some statistics according to the theme.
Keywords: Pre-literate, capacity; stereotypical; discrimination